Economic transformation family structure and poverty rates of black children in metropolitan areas. - Rexroat, Cynthia (American Economic Review, 1989)
Changes in the poverty level of related black children in families in the United States are examined for the period 1969-1979. data concern a sample of 45 SMSAs that contained at least 100000 blacks in 1980. The research investigates the extent to which changing family structure family composition and areal economic conditions are associated with changing poverty rates of black children across metropolitan areas. (EXCERPT)